The digest of Justinian. - Watson, Alan, 1933-2018 (University of Pennsylvania Press, 1998)
When Justinian became sole ruler of the Byzantine Empire in A.D. 527, he ordered the preparation of three compilations of Roman law that together formed the Corpus Juris Civilis. These works have become known individually as the Code, which collected the legal pronouncements of the Roman emperors, the Institutes, an elementary student's textbook, and the Digest, by far the largest and most highly prized of the three compilations. The Digest was assembled by a team of sixteen academic lawyers commissioned by Justinian in 533 to cull everything of value from earlier Roman law. It was for centuries the focal point of legal education in the West and remains today an unprecedented collection of the commentaries of Roman jurists on the civil law.Commissioned by the Commonwealth Fund in 1978, Alan Watson assembled a team of thirty specialists to produce this magisterial translation, which was first completed and published in 1985 with Theodor Mommsen's Latin text of 1878 on facing pages. This paperback edition presents a corrected English-language text alone, with an introduction by Alan Watson.Links to the three other volumes in the set: Volume 1 [Books 1-15]Volume 2 [Books 16-29]Volume 4 [Books 41-50].